(untitled) (Psychology Travelogs, 2023)
This article is devoted to an important problem in education - interpersonal relations in classes where internally displaced students study. Internally displaced students are children who have experienced conflict outbreaks, natural disasters, refugees, resettlement or other forms of migration, and therefore face unique challenges and opportunities in adapting to their new environment. The article examines the influence of such factors as cultural differences, language barriers, trauma and psychological stress on the formation of relationships between internally displaced students and their peers. The authors of the article carefully analyze these aspects and find out how they affect the psychosocial condition of children and the general atmosphere in the classroom. The main purpose of the article is to analyze strategies and programs that contribute to the improvement of interpersonal relations in the classroom, in particular, promoting the development of mutual understanding, inclusion and tolerance. Through practical examples and recommendations for educators and professionals in the field of education and social support, the article provides useful guidance on how to create a safe and supportive environment for internally displaced children in schools. The research aims to identify and implement effective pedagogical techniques and programs aimed at enhancing understanding and empathy among internally displaced students and their peers. The initiatives that foster positive dynamics in the classroom, support tolerant attitudes, and develop collaboration skills in a diverse learning environment are highlighted. The research presented in the article is important for teachers, psychologists, social workers and other professionals who work with internally displaced children. This article promotes awareness of the importance of creating an inclusive and supportive environment for all students, regardless of their background, and helps to strengthen social coexistence in the classroom.